Analisis Strategi Pemasaran Karkas Ayam Broiler untuk Memenuhi Kebutuhan Konsumen pada CV Rejeki Jaya - Habibulloh, Tirmidi Ryan; Wening, Nur (CV. Publikasi Indonesia, 2022)
The high demand for chicken consumption has made the chicken carcass business more competitive. This study aims to formulate a marketing strategy for broiler chicken carcasses at CV, Rejeki Jaya. The research was conducted for six months starting in December 2021. This type of research is descriptive with a qualitative approach. Methods of collecting data are interviews, observations and documentation. The data analysis technique used SWOT analysis. The results showed that the marketing position of CV. Fortune Jaya is in quadrant I so that an aggressive strategy is applied. The right strategy for CV. Rejeki Jaya is: strengthening a solid management team to be able to compete with competitors, improving quality and maintaining prices so that consumers remain loyal, maintaining sufficient stock to anticipate delays due to illness and improving product distribution by prioritizing speed and delivery time. CV. Rejeki Jaya suggested increasing cooperation with chicken farmers by making written contracts to maintain prices and improve product quality so as to win the competition in the chicken carcass business.